The Health Hazard Evaluation Program at NIOSH : reviews of research programs of the National Institute for Occupational Safety and Health (Reviews of research programs of the National Institute for Occupational Safety and Health ;, 2009)
It is the unique mission of the Health Hazard Evaluation Program within the National Institute for Occupational Safety and Health (NIOSH) to respond to requests to investigate potential occupational health hazards. In contrast to other NIOSH programs, the Health Hazard Evaluation Program is not primarily a research program. Rather, it investigates and provides advice to workplaces in response to requests from employers, employees and their representatives, and federal agencies. The National Research Council was charged with evaluating the NIOSH Health Hazard Evaluation Program and determining whether program activities resulted in improvements in workplace practices and decreases in hazardous exposures that cause occupational illnesses. The program was found to play a key role in addressing existing widespread or emerging occupational health issues. This book makes several recommendations that could improve a very strong program including more systematic use of surveillance data to facilitate priority setting, and greater interaction with a broader array of workers, industries, and other government agencies.